2011
DOI: 10.1177/2040622311407542
|View full text |Cite
|
Sign up to set email alerts
|

Unusual asthma syndromes and their management

Abstract: Asthma usually presents with symptoms of wheeze, dyspnoea and cough. However, clinicians should be aware of atypical presentation of this disorder when cough is the main or only symptom in conditions such as cough-variant asthma, nonasthmatic eosinophilic bronchitis and atopic cough. Early diagnosis and treatment of these conditions with inhaled corticosteroids improves symptoms in the majority of patients. Up to 10% of patients with asthma remain poorly controlled in spite of optimal standard therapy. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 138 publications
0
6
0
1
Order By: Relevance
“…The peak expiratory flow (PEF) assessment does not show any variability in CVA patients [2]. The spirometric measurements are normal in patients with CVA [2].…”
Section: Pathological Mechanism Underlying Cvamentioning
confidence: 93%
See 4 more Smart Citations
“…The peak expiratory flow (PEF) assessment does not show any variability in CVA patients [2]. The spirometric measurements are normal in patients with CVA [2].…”
Section: Pathological Mechanism Underlying Cvamentioning
confidence: 93%
“…The results of studies have shown that BAL and sputum in patients with CVA contain an increased percentage of eosinophils [2]. Also, the studies showed that there was no significant difference between CVA and classic asthma in the sputum levels of eosinophilic cationic protein, interleukin 8 (IL-8) and levels of exhaled nitric oxide (FeNO) [2,7,12,17,18]. Studies have suggested that the basic pathophysiological characteristics of CVA are eosinophilic inflammation and AHR [3].…”
Section: Pathological Mechanism Underlying Cvamentioning
confidence: 99%
See 3 more Smart Citations